EFFECTIVENESS OF PROCUREMENT OF CONSTRUCTION MATERIALS AMONG ROAD WORKERS IN EKITI STATE - OJO, OLAOYE AJIBOYE; OLATILU; ANA, AYOKUNLE (Innovare Journal of Social Sciences, 2024)
This study investigated the effectiveness of procurement of construction materials among road workers in Ekiti State. The descriptive research design was used for this study. Sixty copies of structured instrument were developed to collect information from the road construction workers. The data were analyzed using Statistical Package for the Social Science. The research questions were answered using percentage and mean while the hypothesis was analyzed using analysis of variance and tested at 0.05 level of significance. The finding of the study revealed that there is upward increase in the cost of procuring construction materials by workers in Ekiti, several factors such as sequence of materials delivery, availability of material in the local market, material changes in type, and specification during construction among others affect the procurement of construction materials by road workers in Ekiti State. It was revealed that majority of the road construction workers are experienced. It was also revealed that the experience of road construction workers does not influence the factors affecting the procurement of construction materials by workers in Ekiti State. It was recommended among others that concerted efforts should be made by construction industries on ways of procuring construction materials at a cheaper rate to avoid increase in the cost of construction in the State. It was also recommended that there is need to appoint and register procurement experts to manage various procurement of construction materials so that the cost of procurement of materials will be reduced and better attitudes toward the procurement of construction materials should be encouraged among the construction workers.